Australia : Financial Sector Assessment Program-Technical Note-Systemic Risk Oversight and Macroprudential Policy. (IMF Staff Country Reports; Country Report, 2019)
This technical note reviews systematic risk oversight and macroprudential policy in Australia. The paper surveys key concerns affecting the Australian financial system, including the substantial increase in house prices and household indebtedness, the rising concentration of bank exposures, and potential volatility from the commercial real estate sector. The macroprudential policy response of the authorities has also been examined. Current arrangements have historically worked well and are based on a culture of strong inter-agency cooperation, and it is important that processes are appropriate to ensure ongoing focus on stability-related risks. The IMF team recommends that the authorities explore options for further extending their macroprudential toolkit, providing additional flexibility in responding to significant shocks, and reducing systemic vulnerabilities. The slowing in the growth of household indebtedness and lower house prices suggest that substantial new measures are not required at the current juncture, but a 'readiness' assessment would help to facilitate the introduction of new or expanded policy measures when required.